DESIGN AS AN AGENT TO MITIGATE THE HIGH-DENSITY POLYETHYLENE WASTE IN THE AGRICULTURE SECTOR. Reintegration of the end-product in the value chain by developing sustainable products. - Soares, Caroline Chaby Dezerto (2024)
The possibility of carrying out the internship at the circular lab provided an opportunity to combine practical experience with academic knowledge in graphic design and product design, with a special focus on sustainability. The main objective was to solve the problem of high density polyethylene (HDPE) waste in agriculture, through the development of a sustainable design solution to reintegrate material waste into the value chain. This was achieved through the creation of na IOT connected hive called “Buzzhive”. The project included the creation of an innovative device to reduce plastic waste, using design thinking and sustainability principles. In addition, graphic design solutions were produced for application to projects on sustainability and technology simultaneously to support the overall objectives of the internship. The results show that the design has the potential to be used to function as a catalyst for environmental progress as it has been successfully designed to be reintegrated into the value chain. Due to time and resource constraints, Buzzhive's electronic and software components were developed only conceptually, with recommendations for future investigation. Despite this limitation, the internship allowed to improve the author's design and problem-solving capabilities, while also contributing to the development of an innovative and relevant solution in sustainability.